2015
DOI: 10.4274/tnd.46354
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Therapy Use in Multiple Sclerosis: A Cross-Sectional Survey

Abstract: Objective: In this study, we aimed to document the use of alternative and complementary therapy (ACT) in multiple sclerosis (MS) patients, and the relationship with socio-demographic characteristics and clinical data of the ACT users. Materials and Methods: We evaluated 101 MS patients followed in our outpatient clinic and living in Eagean district, mostly in central İzmir. All of them completed a questionnaire related to the use of ACT. Patients who had used any type of ACT were statistically compared with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(16 reference statements)
0
3
0
2
Order By: Relevance
“…In addition, a study in Germany found that the majority of complementary and alternative therapies use by people with multiple sclerosis happens in the early stages of the disease as initially they explore all avenues (Kochs et al, 2014). As the participants in this sample had a mean time since diagnosis of 16 years this may explain why complementary and alternative therapies use was lower that most of previous research where, when reported, time since diagnosis was from seven to nine years (Apel et al, 2006;Gedizlioglu et al, 2015).…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…In addition, a study in Germany found that the majority of complementary and alternative therapies use by people with multiple sclerosis happens in the early stages of the disease as initially they explore all avenues (Kochs et al, 2014). As the participants in this sample had a mean time since diagnosis of 16 years this may explain why complementary and alternative therapies use was lower that most of previous research where, when reported, time since diagnosis was from seven to nine years (Apel et al, 2006;Gedizlioglu et al, 2015).…”
Section: Discussionmentioning
confidence: 41%
“…This result was lower than complementary and alternative therapies use in Germany (67%) (Apel et al, 2006), the United States of America (58%) (Stoll et al, 2012) and the Nordic countries (46-58%) (Skovgaard et al, 2012) but higher than complementary and alternative therapies use in Turkey (26%) (Gedizlioglu et al, 2015). The majority of the participants in the studies which reported higher complementary and alternative therapies usage had relapsing remitting multiple sclerosis and were mildly or moderately affected.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Gedizoğlu ve ark. (11) çalışmasında ise, hastaların en az bir TAT kullanım sıklığı %25.7 olarak belirlenmiştir.…”
Section: Ms Hastalığında Tamamlayıcı Terapilerin Kullanımıunclassified
“…TAT yöntemlerinden haberdar olan hastalar, en çok akrabalarını haber kaynağı olarak göstermiştir. Diğer haber kaynaklarının ise internet, yazılı basın ve %3'lük bir bölümünün ise diğer MS hastaları olduğunu belirtmişlerdir (11) . MS hastalarının %50 ile %75'inin medikal tedavilerden memnun olmaması nedeniyle TAT yöntemlerine başvurduğu, TAT kullananlarda semptomların şiddetinde azalma görüldüğü belirtilmiştir (12,13) .…”
Section: Ms Hastalığında Tamamlayıcı Terapilerin Kullanımıunclassified